Effect of elevation, habitat, and season in butterfly (Lepidoptera: Papilionoidea) assemblages in a tropical mountain - Matamoros-Calderón, Wendolyn; Murillo Hiller, Ricardo; Cerdas Cedeño, Álvaro; Hanson Snortum, Paul; Canet Moya, Noemi; Chacón-Madrigal, Eduardo (Revista de Biología Tropical, 2025)
Introduction: Spatial and temporal variation in the environment promotes biological diversity. However, the combined effects of elevation, seasonality, and habitat on butterfly diversity and abundance are still underexplored in rural tropical ecosystems. Butterflies, as bioindicators, offer an excellent opportunity to assess environmental impacts due to their sensitivity to changes in habitat. Objective: This study aimed to evaluate the variation in butterfly abundance and species richness across different habitats, elevations, and seasons in a rural tropical mountain landscape in Costa Rica. Methods: The study was conducted over six months, encompassing dry and rainy seasons. Butterflies were sampled along an elevational gradient (1200, 1500, and 1800 m) across two habitat types: grasslands and riparian forests. Sampling methods included hand nets and fruit baits in each transect and at each site over six months. We made six visits to each site, with seven transects sampled per visit to capture butterflies. We recorded a total of 1421 individuals representing 151 species. Results: The Nymphalidae family exhibited the highest species richness and abundance. Butterfly abundance decreased with increasing elevation, but species richness patterns varied by family. Seasonal variation significantly affected both abundance and richness, with higher values recorded during the rainy season. Based on local abundance, rare species were more commonly found in riparian forests at higher elevations during the wet season. Habitat did not significantly influence overall butterfly abundance or richness. Conclusions: Seasonality and elevation influence butterfly populations in tropical mountain ecosystems. The lack of a significant habitat effect suggests that other ecological variables may mediate habitat impacts. Further studies are required to clarify these dynamics, particularly the role of habitat heterogeneity.